Integrated traditional Chinese and western medicine nursing based on integration of medical care for pain control in a patient with diabetic foot gangrene complicated with infection (医护一体化模式下1例脱疽患者疼痛的中西医结合护理体会) - ZHENG Wen (郑雯); ZHI Hui (智慧); LIU Jinjing (刘津京); GU Hancheng (顾汉城); SHI Qinggang (石庆刚); WANG Meiyu (王美玉); TONG Fenfei (仝粉飞) (中西医结合护理)
To investigate the effect of integration of medical care for pain control of a patient with diabetic foot gangrene complicated with infection. The clinical data of a patient with diabetic foot gangrene complicated with infection were retrospectively analyzed. Based on the integration of medical care, integrated Traditional Chinese and western medicine nursing interventions such as integration nursing ward round, Traditional Chinese Nursing technique, emotion nursing and health education were carried out to relieve the pain caused by diabetic foot gangrene and improve the patients’ quality of life. (探讨医护协作护理模式在脱疽(糖尿病足坏疽合并感染)患者疼痛护理中的应用效果。回顾性分析科室收治的1例糖尿病足坏疽合并感染患者的临床资料, 通过运用医护一体化护理模式, 给予患者中西医结合护理, 包括医护一体化查房、中医护理技术、情志护理和健康指导, 旨在有效缓解疼痛, 提高患者生活质量 。)